2018
DOI: 10.2196/jmir.9821
|View full text |Cite
|
Sign up to set email alerts
|

Traditional and Web-Based Technologies to Improve Partner Notification Following Syphilis Diagnosis Among Men Who Have Sex With Men in Lima, Peru: Pilot Randomized Controlled Trial

Abstract: BackgroundPatient-initiated partner notification (PN) following the diagnosis of a sexually transmitted infection is a critical component of disease control in men who have sex with men (MSM) sexual networks. Both printed and internet-based technologies offer potential tools to enhance traditional partner notification approaches among MSM in resource-limited settings.ObjectiveThis randomized controlled trial aimed to evaluate the effect of 2 different PN technologies on notification outcomes following syphilis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Meanwhile, the second trial offered a personalized and interactive web application so-called "Game plan" and standard post-evaluation counseling [91]. As compared to the control group (receiving only standard of care), both studies successfully achieved preferable outcomes in the intervention group, including higher likelihood of notifying sex partners (odds ratio, OR = 2.18, 95% CI 1.30-3.66; p = 0.003) in the former study [95], or significant reduction of alcohol use (risk ratio, RR = 0.83, p = 0.047) and number of sex partners (RR = 0.50, p < 0.001) in the latter intervention [91].…”
Section: Web-based Intervention (N = 22)mentioning
confidence: 96%
See 2 more Smart Citations
“…Meanwhile, the second trial offered a personalized and interactive web application so-called "Game plan" and standard post-evaluation counseling [91]. As compared to the control group (receiving only standard of care), both studies successfully achieved preferable outcomes in the intervention group, including higher likelihood of notifying sex partners (odds ratio, OR = 2.18, 95% CI 1.30-3.66; p = 0.003) in the former study [95], or significant reduction of alcohol use (risk ratio, RR = 0.83, p = 0.047) and number of sex partners (RR = 0.50, p < 0.001) in the latter intervention [91].…”
Section: Web-based Intervention (N = 22)mentioning
confidence: 96%
“…Two recent web-based pilot RCTs were conducted by Clark et al to test partner notification for syphilis diagnosis Fig. 3 Mean retention rates by different duration of follow-ups [95], and by Wray et al to examine trial's effectiveness in reducing alcohol use problem and sexual risk behaviors [91]. The first trial employed a web-based partner notification with or without referral cards, which informed available testing and treatment resources for syphilis testing [95].…”
Section: Web-based Intervention (N = 22)mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of emails and text messages to notify contacts has been used most frequently in partner notification for HIV and other sexually transmitted diseases (STDs), such as gonorrhea, syphilis, and chlamydia [4][5][6][7][8][9][10][11]. Previous studies on both patient-initiated (where the individual positive for the disease alerts their contacts) and health care provider-initiated digital contact or partner notification have concluded that the use of emails and/or text messages to notify contacts increases the total number of contacts alerted when used in addition to traditional in-person, telephone-based, or written partner notification [5][6][7][8][9]. This method allows for the ability to reach populations that are inaccessible or hard to reach with traditional partner notification [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The rate of PN varies in different studies: 53% successful direct patient referral in sub-Saharan Africa [11], 73% successful PN in Sweden [18], 76.4% successful PN in the United States [19], and 51% successful PN by patient referral card in Peru [20]. Also, improving the efficacy of PN was found to be more cost-effective than increasing the coverage of CT screening [10].…”
Section: Introductionmentioning
confidence: 99%